Lead (Pb) Biosorption by Intact Biomass and Alginate Extract of Sargassum crassifolium Originated from Gresik Regency Waters - Faisol Mas’ud; Muhammad Browijoyo Santanumurti; Mohamed Hosny Gabr; Mamdouh T Jamal; Norma Aprilia Fanni; Moch Saad (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
The fisheries potential in Gresik Regency is in danger from industrial lead (Pb) pollution. One possible solution is using Sargassum crassifolium, which acts as an absorbent to eliminate Pb in waters. S. crassifolium is characterized by its great affinity for metal cations to bind heavy metal content. This study aimed at finding the effect of S. crassifolium in different forms (wet, dry, and alginate) to absorb Pb content in water. This research was conducted from July to September 2020. The water sample was taken from Gresik Regency and S. crassifolium was obtained from farmers in Talango Island, Sumenep District, Madura. The effectiveness test of the three treatments was conducted based on contact time and biomass factor. Based on the contact time, each treatment was compared with the contact time (1, 7, and 14 days) with 10 g mass per treatment. Meanwhile, for the biomass factor, each treatment was compared by weight (10, 20, and 30 g) for 7 days. The contact time showed that in 14 days, the alginate form of S. crassifolium had the highest absorbent power with 1.370±0.0034 mg.L-1 of lead absorbed and 100% absorbed value. Based on the absorbent mass treatment, 10 g alginate gave the best result with the absorbed lead of 1.364±0.0028 mg.L-1 and an absorption value of 99.71%. The water quality showed that parameters of Dissolved Oxygen (DO), salinity, and nitrates from Gresik Regency were not above standard due to heavy metal pollution. S. crassifolium treatment could decrease the nitrite and nitrate values while increasing DO although still below the standard. This study indicated that 10 g alginate of S. crassifolium in 14 days was effective as a bio-absorbent for Pb heavy metal.